Acceptance and rejection of “morally challenging” behaviour in online sperm donation communities: narrative interviews with recipients and donors - Forshall, Georgina C.; Jones, Georgina L.; Turner-Moore, Rhys (Frontiers in Reproductive Health, 2024)
Introduction Online sperm donation allows those hoping to conceive a baby (“recipients”) to meet prospective sperm donors online, via “connection” websites or social media. These sites offer some advantages to clinical donation (including lower costs and greater choice over donation arrangements) but previous research has suggested that these sites may also pose risks and challenges to those who use them. Therefore, the aim of this exploratory research was to better understand online sperm donation communities and the experiences of both recipients and donors, particularly with respect to situations that could be “morally challenging” or involve harm. Methods Three prolific donors and five recipients were interviewed using an in-depth narrative approach. Carol Gilligan's Listening Guide was employed to analyse the data. Results The findings demonstrated that the donors sought to find ways to maintain autonomy in their donating practices and were concerned about the character and parenting abilities of recipients, as well as the potential for recipients to make unwarranted complaints. The recipients were concerned about their safety and finding a donor they could trust, discussing issues relating to donor “dishonesty”, online abuse, and a lack of support from connection sites and related authorities. Both donors and recipients identified “morally challenging” behaviour relating to donor anonymity (donor use of fake online profiles or aliases) and the sexual motivations or (mis)conduct of some donors. The participants each discussed the ways in which they managed perceived risks. Discussion The degree to which the participants voiced their acceptance or rejection of challenging behaviour in online sperm donation communities varied across and within participants, highlighting the complexity of the way in which people interact in this environment. Further research is required to understand how this form of sperm donation can be as safe and supportive as possible, while also respecting the importance to donors and recipients of autonomy and choice when making donation arrangements.